Wavelengths of your song - Schönmaier, Eleonore (Hugh MacLennan poetry series, 2013)
At night we swim / following the fence: / diverted / we enter the net / shaped like a heart / and in the heart the hook / guides us to the back A stunning unfolding of memory, Wavelengths of Your Song juxtaposes a childhood in the northern Canadian wilderness with the adventures of an international creative life. Genuine environmentalism is at the heart of this collection. Migrations of birds and humans lend their songs to the vivid writing and a tangible, sensory reality emerges from their sounds. Music by Beethoven and Rzewski, paintings by Norval Morrisseau and Kandinsky, and writing by Kafka and Celan, inspire Eleonore Sch?nmaier's poetry. She takes the reader on unexpected journeys skiing across frozen lakes, cycling along Dutch canals, or hiking in Malta and New Zealand. With surprising, at times breathtaking connections, she illuminates hot air ballooning, canoe camping, planting trees on Vienna rooftops, and the bathing of a black horse in the North Sea. In poems that travel extensively around the globe, in lists for living well, and in love letters, Eleonore Sch?nmaier takes the reader on a journey along the wavelengths of the ocean, sound, and the physics of light.